2015
DOI: 10.1002/2014tc003816
|View full text |Cite
|
Sign up to set email alerts
|

Microseismicity of the Béarn range: Reactivation of inversion and collision structures at the northern edge of the Iberian plate

Abstract: The Béarn range, located to the north of the Axial Zone in the Western Pyrenees, is affected by numerous small-magnitude seismic events. These events overlap an area characterized by specific geological structures which are interpreted to have resulted from multistage extensional and compressional deformation. An analysis of surface geology draped over digital elevation model, together with field investigations, allow identification of two main shortening episodes with differing direction of contraction: D1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 66 publications
3
24
3
1
Order By: Relevance
“…Thrusting was accommodated in the basin by continued slip of the NPFT as well as by the Lakora-Larra thrust, which experienced its period of major displacement. It should be noted that, at variance with a previous interpretation of Teixell (1998) and Dumont et al (2015), the Lakora thrust is envisaged as a detachment structure, not rooted in a south-directed crustal ramp. It is difficult to ascertain the precise time when the protocollision initiated.…”
Section: Sequential Restoration Of the Orogenic Evolutionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thrusting was accommodated in the basin by continued slip of the NPFT as well as by the Lakora-Larra thrust, which experienced its period of major displacement. It should be noted that, at variance with a previous interpretation of Teixell (1998) and Dumont et al (2015), the Lakora thrust is envisaged as a detachment structure, not rooted in a south-directed crustal ramp. It is difficult to ascertain the precise time when the protocollision initiated.…”
Section: Sequential Restoration Of the Orogenic Evolutionmentioning
confidence: 64%
“…The deep crustal structure is based on the interpretation of the ECORS-Arzacq seismic reflection profile and on receiver functions analysis of the PYROPE and older surveys (see text). The stippled area represents the cluster of microseisms characteristic of the North-Pyrenean Zone projected after Souriau et al (2014), where the vertical precision of the seismic event location is of 3 km (Dumont et al, 2015). Inset boxes represent key features of the Mesozoic and Cenozoic basins for the reconstruction of the preorogenic architecture shown in …”
Section: Discussionmentioning
confidence: 99%
“…This folding phase which was known long ago (Canérot, 1964) has been recently outlighted in the Ossau North Pyrenean Zone where it is interpreted as a north-verging D2 phase following the south-verging D1 phase (Dumont et al, 2015). This second step of deformation generating NW vergent structures is in fact known in different points of the Western Pyrenees specially to the west of Adour Valley.…”
Section: The Transverse Ossau Thrust Faultmentioning
confidence: 87%
“…Their geometry and general organisation evidence, as in the central Pyrenees, the continental subduction of the Iberian crust under the European one which, here in the Western Pyrenees, occurred near the beginning of the Tertiary period. Their recent interpretation (Dumont et al, 2015) as a result of a southward oriented thrust D1 is not observed. The European crust is in fact involved in a regional northern check structure and the considered southward thrust folds and imbrications observed in the "Chaînons Béarnais" zone, within the Iberian crust, correspond actually to a superficial response to the northward underthrust of southern units.…”
Section: The W-e Oriented Strike Folds and Thrust Faultsmentioning
confidence: 89%
See 1 more Smart Citation